2019
DOI: 10.1111/jdv.15575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anal carcinoma screening in male and female HIV patients at an interdisciplinary HIV therapy centre

Abstract: Background Incidence of anal carcinoma is increased in people living with HIV (PLWH). Due to the improved life expectancy in PLWH, identifying appropriate prevention strategies for non‐AIDS‐defining cancer types such as anal carcinoma has become a priority in managing PLWH today. Objective We aimed to evaluate anal cytology assessment as screening tool for anal dysplasia and/or carcinoma in PLWH, regardless of gender or sexual orientation. Additionally, we investigated the correlation between cancer risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(138 reference statements)
1
2
2
1
Order By: Relevance
“…Previous studies suggested smoking was a risk factor for anal dysplasia and cancer 8,27 . However, in this study we did not confirm this association.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous studies suggested smoking was a risk factor for anal dysplasia and cancer 8,27 . However, in this study we did not confirm this association.…”
Section: Discussioncontrasting
confidence: 99%
“…After adjusting for age, smoking habits, number of sexual partners in the previous year, concomitant STIs, nadir CD4 cell count and HIV RNA load, the presence of perianal warts was an independent risk factor for an abnormal anal cytology. These results are in line with previous studies 27 …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations